2022
DOI: 10.1093/ijnp/pyac015
|View full text |Cite
|
Sign up to set email alerts
|

Butyric Acid Precursor Tributyrin Modulates Hippocampal Synaptic Plasticity and Prevents Spatial Memory Deficits: Role of PPARγ and AMPK

Abstract: Background Short chain fatty acids (SCFA), such as butyric acid (BA), derived from the intestinal fermentation of dietary fiber and contained in dairy products, are gaining interest in relation to their possible beneficial effects on neuropsychological disorders Methods C57BL/6J male mice were used to investigate the effect of tributyrin (TB), a prodrug of BA, on hippocampus (HIP)-dependent spatial memory, HIP synaptic transm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…For a long time, TB was regarded as a precursor of butyric acid [7,20,21] since early several in vitro studies on different cancer cell lines showed that TB can induce apoptosis at millmolar levels. Accordingly, Watkins et al…”
Section: Discussionmentioning
confidence: 99%
“…For a long time, TB was regarded as a precursor of butyric acid [7,20,21] since early several in vitro studies on different cancer cell lines showed that TB can induce apoptosis at millmolar levels. Accordingly, Watkins et al…”
Section: Discussionmentioning
confidence: 99%
“…[ 61 ] SCFAs are organic fatty acids that contain 1–6 carbon atoms. [ 62 ] Butyrate is the main energy source for gut epithelial cells, [ 63 ] and is closely associated with metabolism. SCFAs also include formic, acetic, and propionic acids.…”
Section: Relationships Between Gut Microbiota and Ppgmentioning
confidence: 99%